Reactions of Urinary Stones with Glycine, β-Alanine and Hippuric Acid - MAHAPATRA (CHOUDHURY), BASABI; SIDDIQUI, NAGMA; KUMAR, ASHISH; RANI SINHA, MADHU (Asian Journal of Chemistry, 2010)
Insoluble ingradients of the kidney stones (powdered stones and then whole stones) were made to solubilized with glycine, β-alanine and hippuric acid. It was found that the dissolution of stone ingradient in powdered form was much more than the whole stone.